Challenges of Inclusive-Responsive Leadership in Public High Schools: Mapping the Socio-Cultural and Policy Contexts - Sitti Habibah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Despite national mandates for inclusive education, implementing inclusive-responsive leadership in Indonesian public high schools faces complex hurdles. This study maps the challenges of inclusive-responsive leadership by examining the socio-cultural and policy contexts within public high schools in South Sulawesi, exploring how school leaders navigate the gap between formal inclusion regulations and local cultural expectations. Employing a qualitative approach, a multi-site case study design was utilized across several schools. Data were collected through semi-structured interviews with principals and policy stakeholders, alongside regional policy document analysis, and interpreted using thematic analysis focusing on leadership adaptability. The results reveal three primary challenges: (1) policy-practice decoupling, where inclusive regulations lack technical guidelines for local execution; (2) socio-cultural barriers, including traditional paradigms viewing inclusion as a peripheral value; and (3) resource scarcity, specifically a lack of specialized pedagogical training for leaders. The study finds that while leaders show high commitment, their actions are restricted by a compliance-based rather than a value-based approach. This research contributes to educational leadership discourse by providing a localized mapping of inclusion challenges in a non-Western context. It offers insights for policymakers to harmonize national standards with socio-cultural specificities, advocating for a leadership model that is both policy-compliant and culturally responsive.